Identification of Gas Turbine Ground Vortex Formation Regimes - Barata, Jorge M M (2012)
In the present paper the preliminary work of Barata et al.11 on gas turbine ground vortex formation is extended to include eighteen different engines that are presently in service. The ground vortex flows produced by each engine are compared and discussed for the corresponding operational condition. The results have shown that more than one mode can occur for a particular engine-velocity ratio-clearance distance combination with 1, 2 or 3 vortexes that may merge before entering the inlet engine. Further improvement of gas turbine design is then required to prevent hazardous operation of aircrafts in the airports.